2021
DOI: 10.3390/nu13041276
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Safety and Efficacy of Prebiotic Enriched Infant Formula—A Randomized Controlled Trial

Abstract: The present study aims to evaluate the effects of an infant formula supplemented with a mixture of prebiotic short and long chain inulin-type oligosaccharides on health outcomes, safety and tolerance, as well as on fecal microbiota composition during the first year of life. In a prospective, multicenter, randomized, double-blind study, n = 160 healthy term infants under 4 months of age were randomized to receive either an infant formula enriched with 0.8 g/dL of Orafti®Synergy1 or an unsupplemented control for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 33 publications
(10 reference statements)
2
7
0
Order By: Relevance
“…A review of studies that evaluated stool characteristics among infants receiving a mixture of prebiotics found softer stools in the infants receiving formula with prebiotics in 4 out of 5 studies [16]. Multiple other studies have also demonstrated that infant formulas supplemented with prebiotics or mixtures of pre-and probiotics are associated with softer stools [17,[20][21][22][23]. Notably the previous studies are all randomized clinical trials; thus, it is reassuring that similar effects for stooling were observed in our real-world observational study.…”
Section: Discussionsupporting
confidence: 75%
“…A review of studies that evaluated stool characteristics among infants receiving a mixture of prebiotics found softer stools in the infants receiving formula with prebiotics in 4 out of 5 studies [16]. Multiple other studies have also demonstrated that infant formulas supplemented with prebiotics or mixtures of pre-and probiotics are associated with softer stools [17,[20][21][22][23]. Notably the previous studies are all randomized clinical trials; thus, it is reassuring that similar effects for stooling were observed in our real-world observational study.…”
Section: Discussionsupporting
confidence: 75%
“…For prebiotics, significant microbiotal changes have been reported for post-supplement durations of between 2 weeks (Waligora-Dupriet et al, 2007) and 6 months (Salvini et al, 2011), with no information on further progression. Longerlasting impact appears unlikely since differences in the relative abundance of the bifidobacteria, which are characteristic of prebiotic supplementation, are only detected at 2 and 6 months in infants supplemented for 12 months (Neumer et al, 2021). For probiotics, no systematic impact on microbiota composition has been observed (e.g., Rinne et al, 2006vs.…”
Section: Infant Nutrition/feeding Modementioning
confidence: 99%
“…The respondents also reported inulin and FOS as the next best fibers to manage constipation. FOS and inulin have been shown in numerous studies to soften stool and/or increase stool consistency in infants and young children [ 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Unlike in the other regions, GOS were chosen as the second-best fiber to reduce constipation symptoms in Saudi Arabia and Mexico.…”
Section: Discussionmentioning
confidence: 99%